2021
DOI: 10.1007/s00417-020-05057-0
|View full text |Cite
|
Sign up to set email alerts
|

Posterior staphyloma is associated with the microvasculature and microstructure of myopic eyes

Abstract: Objective To investigate the microvasculature and structural characteristics of the eyes of myopic patients and their association with posterior staphyloma (PS). Methods This was a retrospective, case-control study comprising of 106 eyes from 72 individuals. Using 1:1 matching of axial length (AL) of their eyes, patients were allocated into a PS group or no posterior staphyloma (NPS) group. All patients were examined using ultra-widefield fundus imaging, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
6
13
0
Order By: Relevance
“…The RT, CT, and SFST in the macular area of the PS group were lower than those in the NPS group, and GEE indicated that SFST and foveal and parafoveal CT were significantly correlated with PS. This result was consistent with many previous reports ( Hayashi et al, 2013 ; Igarashi-Yokoi et al, 2021 ; Nie et al, 2021 ). Zhou et al also found a significant correlation between PS and choroidal thinning; the higher the relative height of PS, the more serious the choroidal atrophy ( Zhou et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The RT, CT, and SFST in the macular area of the PS group were lower than those in the NPS group, and GEE indicated that SFST and foveal and parafoveal CT were significantly correlated with PS. This result was consistent with many previous reports ( Hayashi et al, 2013 ; Igarashi-Yokoi et al, 2021 ; Nie et al, 2021 ). Zhou et al also found a significant correlation between PS and choroidal thinning; the higher the relative height of PS, the more serious the choroidal atrophy ( Zhou et al, 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…However, we did not find a significant decrease in the SVD of the PS group. This phenomenon has been similarly reported in a previous study ( Nie et al, 2021 ). Another study hypothesized that impaired hemodynamics in myopic eyes is an early sign of a decrease in ocular blood flow in patients with pathological myopia ( Benavente-Pérez et al, 2010 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…When the rotation angle is greater than 15°, ONH may considered as rotation. The angle α between retinal temporal arterial vascular arcades was measured from the center of ONH with 250 pixels radius [5].…”
Section: Parameters From Optos and Ss-octmentioning
confidence: 99%
“…Studies have confirmed that eyes with PS are significantly associated with the worsening of visual acuity and serious anatomical alterations than the non-staphylomatous eyes [3][4][5]. However, few comprehensive and quantitative studies have reported the specific effects of each type of PS on visual outcome and anatomical structure in highly myopic eyes.…”
Section: Introductionmentioning
confidence: 99%